If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(4x + 1) = 10(3x + 2) Reorder the terms: 9(1 + 4x) = 10(3x + 2) (1 * 9 + 4x * 9) = 10(3x + 2) (9 + 36x) = 10(3x + 2) Reorder the terms: 9 + 36x = 10(2 + 3x) 9 + 36x = (2 * 10 + 3x * 10) 9 + 36x = (20 + 30x) Solving 9 + 36x = 20 + 30x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-30x' to each side of the equation. 9 + 36x + -30x = 20 + 30x + -30x Combine like terms: 36x + -30x = 6x 9 + 6x = 20 + 30x + -30x Combine like terms: 30x + -30x = 0 9 + 6x = 20 + 0 9 + 6x = 20 Add '-9' to each side of the equation. 9 + -9 + 6x = 20 + -9 Combine like terms: 9 + -9 = 0 0 + 6x = 20 + -9 6x = 20 + -9 Combine like terms: 20 + -9 = 11 6x = 11 Divide each side by '6'. x = 1.833333333 Simplifying x = 1.833333333
| 0.029x+2x=0.034x | | 2849=37(p+20) | | f(x)=2t-3whatisf(7) | | -3x+5=-2(3x+5) | | 15+(-5x)=15-5x | | 3y+4=-1y+-4 | | -7u+11=-9(u-1) | | 0.029+2x=0.034x | | 2x(2x-5)(5x+2)=0 | | 8(-9p+2)-7p= | | 814=-22a | | -2(x-7)=-4x+20 | | 5v-89=2v+34 | | 3n+35=7n+35 | | 9w-10=2(w+9) | | 5+x^2=65 | | -2x+5=20-x | | 3x(x+2)=3x^2+4x-3+2x | | -3(5y-2)-y=-2(y-2) | | 23=3u+8 | | 8x-3.4=3x-6.7 | | -8d-d+7d=72 | | (w-4/-9)(-2/-3) | | -5(y-3)=-15 | | -8u+2(u+5)=16 | | 2x+3-5=5x-3+3x | | 7-4x=5x | | 2y+3(y-2)=29 | | C=240+0.75Y | | 3(x+4)=2(11-x) | | -2=6(x+3)-2x | | 284=-66a |